Implementasi Protokol DSDV (Destination Sequenced Distance Vector) Pada Mobile Ad-Hoc Network Dengan Menggunakan Perangkat Berbasis nRF24L01 - I Made Oka Semara Putra; Primantara Hari Trisnawan; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
DSDV (Destination Sequenced Distance Vector) Protocol is one of the protocols which was used appropriately for Mobile Ad-Hoc Network, because it was proactive in order to solve the trait of the network which was changeable. However, in implementing process, the DSDV protocol was mostly used in simulator implementation, so that it resulted the study which was in ideal or perfect condition that would be problem when the protocol was implemented in daily life. In order to solve the problem, the researcher implemented the DSDV protocol on mobile ad-hoc network by using nRF24L01 based device in order to know the communication result of node on the real place where the study was done. From the study which was done , it showed that DSDV protocol can be implemented for every node, where every node can send broadcast messages to identify, for changing address each other, and in making routing table. Besides, it was also done the sending process in order to know the communication of node by using two testing scenarios; the first one was when the sender node needed another node in order to process the delivery and it showed the successful percentage which was 70%. The next was the second scenario was when the destination node moved and went into the sender's node range and it showed the successful percentage which was 80%. The result of the implementation which was done showed that the environment which was used as the testing environment affected the communication from node of DSDV protocol.